Effect of Heat Shock on Plant Growth and on Lipid and β-Glucan Syntheses - Ordin, L. (1974)
Primary leaves of 8-day-old Phaseolus vulgaris plants dipped in water at 46.5 to 47.5 C for 2 minutes were found to have decreased synthesis of lipid and β-glucan compared to controls; UDP-glucose was used as substrate by cell-free preparations. As time elapsed, leaf growth, which was inhibited within the first 12 hours recovered in a subsequent 24-hour period. Synthesis of alkali-insoluble glucan by cell-free preparations was stimulated both in absolute and relative terms in the treated leaves at the later time period.